MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA KELAS VII SMPN 1 DOMPU MATERI POKOK HIMPUNAN MELALUI PENERAPAN PENDEKATAN KONSTRUKTIVISME TAHUN PELAJARAN 2011/2012 - Sukarma, I Ketut (Jurnal Ilmiah IKIP Mataram, 2020)
Study properly is learning which is able to interaction and understand study material when itâ€™s running one of the study purposed is learning through contructive approach.The purpose of this research is to improve studentsâ€™ activity and achievement through contructive approach in class VIIÂ SMPN 1 Dompu, Acdemic years 2011/2012 on collecting material. The kind of this research is dealetd with some approaches, there are kualitatif and kuantitatif thad consist of techinigue collecting data, observation and test. Analisis of technique data is observation result of study evaluation. The result found that to carry out teaching and learning on siklus 1 of fulfillment percentage is 31 and study percentage is 73,8%, while students activity is category fairly active on siklus II. The students who fulfil is about 37 and fulfillment percentage is 88,10%, and students activity on category active. It is cloncluded that using constructive approach able to improve study achiement on mathematics of collecting material for students in class VIIÂ SMPN 1 Dompu Academic years 2011/2012.